Hubungan Faktor Internal dan Iklim Keselamatan terhadap Perilaku Keselamatan Pekerja Kantin - Arnys An Nida Isnany; Indri Santiasih; Am Maisarah Disrinama (Jurnal Ilmiah Psikologi MIND SET, 2021)
Incidents in 2018 and 2019 in support company’s canteen involve the same person caused by unsafe action and fatigue. Company never measure the safety climate whereas the company commit to safety. Objectives in this research is to find the relationship of internal factor (gender, age, year working experience and fatigue) and safety climate to safety behavior using chi-square, fisher exact test and kendall tau test also to find the difference of safety behavior by gender, age, and year working experience using kruskal wallis and mann whitney test. Methods in this research are safety observation checklist, Swedish Occupational Fatigue Inventory questionnaire to measure fatigue, Nordic Occupational Safety Climate Questionnaire-50 to measure safety climate. There is a relationship between physical discomfort (fatigue) related to safety behavior (p-value 0,03, correlation coefficient 0,513). There is no difference of safety behavior by gender, age, and year working experience. Recommendations given are to ensure drinking water is available, suggest the workers do warming up before working and provide cool and warm compress near from the first aid box.